2014
DOI: 10.1167/14.5.16
|View full text |Cite
|
Sign up to set email alerts
|

Visual control of an action discrimination in pigeons

Abstract: Recognizing and categorizing behavior is essential for all animals. The visual and cognitive mechanisms underlying such action discriminations are not well understood, especially in nonhuman animals. To identify the visual bases of action discriminations, four pigeons were tested in a go/no-go procedure to examine the contribution of different visual features in a discrimination of walking and running actions by different digital animal models. Two different tests with point-light displays derived from studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 73 publications
3
24
0
1
Order By: Relevance
“…In summary, consistent with previous studies (Dittrich et al 1998;Qadri et al 2014), the present study provides another case in which the pigeons, unlike humans, seem to fail to make the connection between the full-detail displays and their point-light counterparts even if the common motion features of stimuli are available as a cue. Contrary to our prediction, the motion-congruent group showed poorer transfer to point-light displays compared with the motion-incongruent group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In summary, consistent with previous studies (Dittrich et al 1998;Qadri et al 2014), the present study provides another case in which the pigeons, unlike humans, seem to fail to make the connection between the full-detail displays and their point-light counterparts even if the common motion features of stimuli are available as a cue. Contrary to our prediction, the motion-congruent group showed poorer transfer to point-light displays compared with the motion-incongruent group.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies reported that pigeons failed to transfer motion discrimination to point-light displays (Dittrich et al 1998;Qadri et al 2014). In those studies, the overall dissimilarity of point-light and full-detail displays greatly reduced peck rates to the point-light displays during transfer tests, resulting in poor discrimination of the pointlight test stimuli.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…That the processing of PLDs and full-figured complete displays is not equivalent is further supported by studies of action recognition using digital models (Asen & Cook, 2012; Qadri, Asen, & Cook, 2014; Qadri, Sayde, & Cook, 2014). After training pigeons to discriminate complete, digitally rendered animal models engaged in either walking or running actions (Asen & Cook, 2012), Qadri, Asen, and Cook (2014) found that the discrimination of these action categories did not transfer to PLD models that were built using the same articulated structure, motion, and background as the trained actions.…”
Section: Dot-based Perceptual Groupingmentioning
confidence: 93%
“…After training pigeons to discriminate complete, digitally rendered animal models engaged in either walking or running actions (Asen & Cook, 2012), Qadri, Asen, and Cook (2014) found that the discrimination of these action categories did not transfer to PLD models that were built using the same articulated structure, motion, and background as the trained actions. This result persisted across differences in the size of the defining dots and changes in the overall visual angle of the display, both changes designed to promote the perceptual grouping of the separated dots.…”
Section: Dot-based Perceptual Groupingmentioning
confidence: 99%